2012
DOI: 10.1039/c2an35722d
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-enhanced Raman spectroscopy with optical feedback cw diode lasers for gas phase analysis and spectroscopy

Abstract: A variant of cavity-enhanced Raman spectroscopy (CERS) is introduced, in which diode laser radiation at 635 nm is coupled into an external linear optical cavity composed of two highly reflective mirrors. Using optical feedback stabilisation, build-up of circulating laser power by 3 orders of magnitude occurs. Strong Raman signals are collected in forward scattering geometry. Gas phase CERS spectra of H(2), air, CH(4) and benzene are recorded to demonstrate the potential for analytical applications and fundamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 30 publications
4
96
0
Order By: Relevance
“…A previous study reported a detection limit of 480 ppm for hydrogen using CERS based on spontaneous Raman scattering with an incoherent Raman process. 11 Therefore, we expect that our approach will achieve a detection limit on the ppb level because it is based on a CARS process with an intrinsic coherent Raman process. This approach has the potential to lead to a high-sensitivity, highly selective, and real-time monitoring tool for the detection of trace isotopes, especially diatomic molecules, including radioactive hydrogen isotopes, which are infrared inactive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported a detection limit of 480 ppm for hydrogen using CERS based on spontaneous Raman scattering with an incoherent Raman process. 11 Therefore, we expect that our approach will achieve a detection limit on the ppb level because it is based on a CARS process with an intrinsic coherent Raman process. This approach has the potential to lead to a high-sensitivity, highly selective, and real-time monitoring tool for the detection of trace isotopes, especially diatomic molecules, including radioactive hydrogen isotopes, which are infrared inactive.…”
Section: Discussionmentioning
confidence: 99%
“…11 In fact, coherent anti-Stokes Raman scattering (CARS) microscopy has excellent sensitivity, comparable to that of fluorescent microscopy, but without the need for staining. 13 Since the coherent Raman process generally generates signals 10 5 -10 7 times higher than the incoherent spontaneous Raman process, CERS incorporating a coherent Raman process has great potential as a detection tool for gas-phase chemical species that are otherwise difficult to detect using conventional absorption-based spectroscopic methods and will become an attractive alternative to CEAS and CRDS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a laser with relatively low power could be employed (0.1 W, argon ion). High sensitivity with a low-power laser was also achieved by Hippler et al [54]. They built a cavity, in which the radiation of a diode laser (10 mW, 635 nm) was enhanced by three orders of magnitude to measure hydrogen, methane and benzene vapor.…”
Section: Natural Gasmentioning
confidence: 99%
“…Sample gas is pumped into the optical cavity to interact with the intense laser light. A recent study demonstrated low ppm or even ppb level detection limit using cavity-enhanced Raman spectroscopy to detect H 2 , N 2 , and other gases (Salter et al 2012). In this experiment, a 10-mW single-mode diode laser at 635 nm was used.…”
Section: Promising Research and Developmentmentioning
confidence: 99%